Strategi Pemasaran Masyarakat Terhadap Mobile Banking Pada Bank 9 Jambi Syariah di Wilayah Kota Jambi - Nurul Wirdah; Usdeldi Usdeldi; Nur Fitri Martaliah (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to examine the community marketing strategy for mobile banking at Bank 9 Jambi Syariah in Jambi City and its constraints. The problem in this study is that Bank 9 Jambi Syariah is one of the most popular banks among the community. Mobile banking services allow customers to conduct various transactions without the need for a banker, such as transferring money between accounts. Other banks also offer mobile banking services, but Bank 9 Jambi's customer base has grown significantly. What is the community marketing strategy for mobile banking at Bank 9 Jambi Syariah in Jambi City? To answer this question, the researcher used a qualitative research approach. The sample used in this study was Bank 9 Jambi Syariah, located in Jambi City. The analysis used in this study was descriptive qualitative analysis. The results of this study indicate that Bank 9 Jambi Syariah's community marketing strategy for mobile banking in Jambi City. The aim is to increase promotional activities, minimize tariff strategies with optimal results, and streamline the registration process. The challenge faced by Bank 9 Jambi Syariah in marketing its mobile banking services lies in promotion. Bank 9 Jambi's promotions have been poorly received by rural communities due to a lack of technological understanding and limited outreach.